Protein-Losing Enteropathy Demonstrated by 99mTc-ASC Lymphoscintigraphy - Jingnan Wang; Hongli Jing; Fang Li (Diagnostics, 2025)
A 30-year-old woman presented with progressive edema and mild diarrhea. Laboratory examination revealed hypoalbuminemia. She underwent 99mTc-antimony sulphide colloid (99mTc-ASC) lymphoscintigraphy to evaluate potential loss of protein through gastrointestinal tract caused by lymphatic leakage and detect abnormalities in the lymphatic systems. The images showed abnormal leakage of radiotracers in the bowel, suggestive of protein loss through the gastrointestinal tract. Abnormal visualization of the lower part of thoracic duct and bilateral venous angle was also demonstrated on 99mTc-ASC scintigraphy. It suggested secondary intestinal lymphangiectasis caused by lymphatic obstruction and reflux. Enhanced CT reconstruction of the small intestine revealed roughness and thickening of intestinal wall, consistent with the diagnosis of protein-losing enteropathy.